Respuesta del banano a la aplicación de acondicionadores y mejoradores de suelo - Quintana Gallegos, Pedro Francisco (2006)
In the farm Sta. Inés of property of the University of Machala, located to 5 km of the Cantón Machala, Province of The Oro, the answer was investigat ed from the banana tree to the application of conditioners and soil mejoradores. The planed objectives were: 1. To determine the answer from the banana tree to the application of conditioners and soil mejoradores. 2. To evaluate the conditions physique, chemical and biological of the soil in the pre and post application. In the banana farm a share was select with the appropriate conditions for the test. The treatments were: agroroot (2 l /ha), acosalsod (2 l/ha), zeoagro (2 sacks /ha), zeoagro + fert. Chemistry (2 sacos/ha), agroroot + Acosalsod (1 l: 2 l) and the witness. It was select for each treatment 4 experimental units, with a height of 70 cm to 1 m, the application was directed to the fertilization area in form manual and with a backpack bomb with a frequency of 30 days. It is registered the data from the beginning of the application until the emission to foliate of the variable diameter, height, number of leaves; the yield in the packer plant, for the variables weight of the raceme, number of hands, calibration second and last hand, longitude of second and last hand, evaluation of damages. The design experimental employed was that of Blocks at random with units in free competition, It`s carried out 3 replicas for each treatment distributed in an area of 4 ha approximately. The results obtained at field level indicate that the agronomic variables were significant, It didn't seize of yield; the most excellent in the treatments was the 4 (zeoagro+fert. chemistry) that obtained the best average in diameter, height, number of leaves, weight of the raceme and number of hands, followed by the treatment 5 (agroroot+acosalsod) with the best longitude of hands.